Peripheralized sepiapterin reductase inhibition as a safe analgesic therapy - Cronin, Shane J. F.; Andrews, Nick A.; Latremoliere, Alban (Frontiers in Pharmacology, 2023)
The development of novel analgesics for chronic pain in the last two decades has proven virtually intractable, typically failing due to lack of efficacy and dose-limiting side effects. Identified through unbiased gene expression profiling experiments in rats and confirmed by human genome-wide association studies, the role of excessive tetrahydrobiopterin (BH4) in chronic pain has been validated by numerous clinical and preclinical studies. BH4 is an essential cofactor for aromatic amino acid hydroxylases, nitric oxide synthases, and alkylglycerol monooxygenase so a lack of BH4 leads to a range of symptoms in the periphery and central nervous system (CNS). An ideal therapeutic goal therefore would be to block excessive BH4 production, while preventing potential BH4 rundown. In this review, we make the case that sepiapterin reductase (SPR) inhibition restricted to the periphery (i.e. excluded from the spinal cord and brain), is an efficacious and safe target to alleviate chronic pain. First, we describe how different cell types that engage in BH4 overproduction and contribute to pain hypersensitivity, are themselves restricted to peripheral tissues and show their blockade is sufficient to alleviate pain. We discuss the likely safety profile of peripherally restricted SPR inhibition based on human genetic data, the biochemical alternate routes of BH4 production in various tissues and species, and the potential pitfalls to predictive translation when using rodents. Finally, we propose and discuss possible formulation and molecular strategies to achieve peripherally restricted, potent SPR inhibition to treat not only chronic pain but other conditions where excessive BH4 has been demonstrated to be pathological.